Marjin Pemasaran Cengkeh Di Desa Tompasobaru Satu Kecamatan Tompasobaru - Pinontoan, Keni Angga; Rumagit, Grace Adonia Josefina; Rori, Yolanda Pinky Ivanna (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2023)
The results of this study show that the clove marketing channel in Tompaso Baru Satu Village involves marketing institutions, namely collecting traders. Collecting traders buy cloves from farmers or producers then sorting is carried out, after that the cloves are packaged and then sold to wholesalers in Manado City using land transportation, namely pickup cars or trucks depending on the availability of cloves. Farmers or producers sell cloves to collecting traders at a price of Rp. 110,000 per kg, where the price is determined by the collecting merchant. In its sale, farmers or producers spend Rp. 51 per kg for sacks and transportation of Rp. 58 per kg, with a total marketing cost of Rp. 109 per kg. The profit obtained by farmers or producers after deducting marketing costs is Rp. 109,891 per kg. Collecting traders sell cloves to wholesalers at a price of Rp. 135,000 per kg. In its sales, collecting traders incur labor costs of Rp. 522 per kg, packaging costs of Rp. 52 per kg and transportation costs of Rp. 435 per kg. The marketing margin obtained by collecting traders is Rp. 25,000 per kg with profits obtained after deducting marketing costs of Rp. 23,994 per kg.